2018
DOI: 10.1093/carcin/bgy095
|View full text |Cite
|
Sign up to set email alerts
|

Trop-2 plasticity is controlled by epithelial-to-mesenchymal transition

Abstract: The cell surface glycoprotein Trop-2 is commonly overexpressed in carcinomas and represents an exceptional antigen for targeted therapy. Here, we provide evidence that surface Trop-2 expression is functionally connected with an epithelial phenotype in breast and prostate cell lines and in patient tumor samples. We further show that Trop-2 expression is suppressed epigenetically or through the action of epithelial-to-mesenchymal transition transcription factors and that deregulation of Trop-2 expression is link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Low Trop2 expression associates with poor overall survival, invasion, and poor differentiation in hepatocellular carcinomas [ 88 ], but not in cholangiocarcinomas [ 75 ]. Similarly, our study shows that in lymph-node-positive breast cancer and prostate cancer patients, low expression of TACSTD2 mRNA associates with worse prognosis [ 137 ].…”
Section: Trop2 In Cancermentioning
confidence: 79%
See 3 more Smart Citations
“…Low Trop2 expression associates with poor overall survival, invasion, and poor differentiation in hepatocellular carcinomas [ 88 ], but not in cholangiocarcinomas [ 75 ]. Similarly, our study shows that in lymph-node-positive breast cancer and prostate cancer patients, low expression of TACSTD2 mRNA associates with worse prognosis [ 137 ].…”
Section: Trop2 In Cancermentioning
confidence: 79%
“…Other miRNAs that target Trop2 were also identified in head-and-neck carcinoma [ 134 ] and urothelial bladder cancer [ 135 ]. Furthermore, we and others showed that Trop2 expression is regulated by methylation of TACSTD2 gene promoter in various cancer cells [ 73 , 75 , 88 , 136 , 137 ]. Importantly, Lin et al found hypermethylation of TACSTD2 gene promoter in lung adenocarcinoma tissues and cell lines explaining low expression of Trop2 in this type of cancer [ 73 ].…”
Section: Trop2 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The epithelial and mesenchymal sublines were established from sorted single cell clones derived from Trop-2 positive or Trop-2 negative populations, as shown in Remsik et al . 25 . PC-3 cells were cultivated in Ham’s F12 media (TFS) with 10% of FBS, penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%